Experimental Investigation of Virgin and Reclaimed Asphalt Modified Bituminous Synthesis - Sandeep Singh, Jasgurpreet Singh (International Journal of Advanced Science and Technology, 2020)
In recent years there was a gradual increase in construction and demolition wastes. It has resulted in waste disposal problem due to shortage of available landfills. Reuse of these materials after proper recycling has become trending practice, as it is cost effective. However, before using such materials the mechanical properties must be tested and suitable blending is done if required. The percentage of Recycled Asphalt is chosen at different levels by various researchers. But in this work we take a range of Recycled Asphalt from 10% to 50% and check the best one percentage of Recycled Asphalt to be used in road construction.